2017
DOI: 10.5459/bnzsee.50.2.73-84
|View full text |Cite
|
Sign up to set email alerts
|

The Mw7.8 2016 Kaikōura earthquake

Abstract: We provide a summary of the surface fault ruptures produced by the Mw7.8 14 November 2016 Kaikōura earthquake, including examples of damage to engineered structures, transportation networks and farming infrastructure produced by direct fault surface rupture displacement. We also provide an overview of the earthquake in the context of the earthquake source model and estimated ground motions from the current (2010) version of the National Seismic Hazard Model (NSHM) for New Zealand. A total of 21 faults ruptured… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(12 citation statements)
references
References 15 publications
1
11
0
Order By: Relevance
“…In several places along the coast, multiple strands strike adjacently to each other (Ryan et al, 2009;Sahakian et al, 2017), adding complexity to models of major NIRC strands rupturing together. Recent studies of multi-fault earthquake propagation, as observed in the recent 2016 Kaikōura Earthquake in New Zealand (Clark et al, 2017;Hamling et al, 2017;Kaiser et al, 2017;Stirling et al, 2017), revealed complex and cascading fault linkages that control rupture lengths and potential earthquake magnitudes.…”
Section: Introduction Geologic Background and Motivationmentioning
confidence: 99%
“…In several places along the coast, multiple strands strike adjacently to each other (Ryan et al, 2009;Sahakian et al, 2017), adding complexity to models of major NIRC strands rupturing together. Recent studies of multi-fault earthquake propagation, as observed in the recent 2016 Kaikōura Earthquake in New Zealand (Clark et al, 2017;Hamling et al, 2017;Kaiser et al, 2017;Stirling et al, 2017), revealed complex and cascading fault linkages that control rupture lengths and potential earthquake magnitudes.…”
Section: Introduction Geologic Background and Motivationmentioning
confidence: 99%
“…Asymmetric offset distributions along fault ruptures have been reported for many seismic events (e.g., Stein et al, 1997;Lin et al, 2002;Manighetti et al, 2005;Wesnousky, 2008;Stirling et al, 2017). Hence, we consider that the displacement identified in the walls of the Alviela trench may not be representative of the overall surface displacement produced by the earthquake.…”
Section: Discussionmentioning
confidence: 95%
“…At least 21 faults ruptured on and offshore of the north-east of the South Island of New Zealand (Figure 4). The ruptures began on The Humps Fault near Waiau and continued north-eastwards for ~180 km [15]. Ground shaking was strongest in the epicentral region near Culverden, and to the northeast between Kekerengu and Seddon (Figure 5).…”
Section: Ground Shakingmentioning
confidence: 99%